Capital Structure in MENA Region: A Panel Data Analysis (Global Journal of Management and Business Research, 2019)
In this paper we make an attempt to provide some insight into the capital structure choice of the MENA region for the period 2006-2015. We develop a dynamic panel data model that explicitly takes into account the determinants of capital structure choice. It has been concluded that factors such as size, profitability, asset tangibility and rating have significant impact on the leverage structure by firms in the MENA region context.
Keywords: determinants of capital structure choice; MENA region